ESTRATÉGIAS ENUNCIATIVAS E EFEITOS DE SENTIDO EM CAMPANHA POLÍTICA PRESIDENCIÁVEL: UMA ANÁLISE SEMIÓTICA - Dayne da Silva Caldeira Saibert (2020)
Recognized as a theory of signification it postulates the text as its object and is dedicated to explaining what it says and how it does it to say what it says, discursive semiotics is organized through the generative path of meaning, consisting of three levels : the fundamental, the narrative and the discursive, ranging from the most simple and abstract to the most complex and concrete. At this juncture, this research proposes to analyze the enunciative strategies, as well as to understand the effects of meanings in the political propaganda of the actor Jair Bolsonaro during the 2018 electoral process. To this end, five political posters elected through his official Facebook are elected as corpus. In order to achieve the intended objective, it is sought, from the theoretical and methodological assumptions of discursive semiotics, to describe and interpret the content plan, as well as the enunciation instances, the expression plan and the semi-symbolic relations to understand the effects of meaning constructed by the enunciator in the text. To analyze the expression plane, we consider the assumptions of plastic semiotics, thought by Floch (1985), and the studies developed by Pietroforte based on the semiotic concept of semi-symbolism. In order to complement the analysis, it is also apparent, through the notion of ethos, proposed by Discini, based on semiotic postulates, the construction of the image of the politician in the selected posters. The present work is guided by a qualitative interpretative methodology, chosen especially for the analysis of the corpus. Thus, it is pointed out as a result the ways in which the effects of meanings and enunciative strategies in the political campaign of Jair Bolsonaro, associated with a favorable historical-social context, contributed to the adherence of the enunciatee to the conveyed speech. Keywords: Discursive semiotics. Enunciative strategies. Sense effects. Semi symbolism. Political campaign.